A High-Efficiency Artificial Synthetic Pathway for 5-Aminovalerate Production From Biobased L-Lysine in Escherichia coli - Cheng, Jie; Tu, Wenying; Luo, Zhou; Gou, Xinghua; Li, Qiang; Wang, Dan; Zhou, Jingwen (Frontiers in Bioengineering and Biotechnology, 2021)
Bioproduction of 5-aminovalerate (5AVA) from renewable feedstock can support a sustainable biorefinery process to produce bioplastics, such as nylon 5 and nylon 56. In order to achieve the biobased production of 5AVA, a 2-keto-6-aminocaproate-mediated synthetic pathway was established. Combination of L-lysine α-oxidase from Scomber japonicas, α-ketoacid decarboxylase from Lactococcus lactis and aldehyde dehydrogenase from Escherichia coli could achieve the biosynthesis of 5AVA from biobased L-lysine in Escherichia coli. The H2O2 produced by L-lysine α-oxidase was decomposed by the expression of catalase KatE. Finally, 52.24 g/L of 5AVA were obtained through fed-batch fermentation. Moreover, homology modelling, molecular docking and molecular dynamic simulation analyses were used to identify mutation sites and propose a possible trait-improvement strategy: the expanded catalytic channel of mutant and more hydrogen bonds formed were beneficial for the substrates stretch. In summary, we have developed a promising artificial pathway for efficient 5AVA synthesis.